Critical heat flux for flow boiling of water on micro-structured Zircaloy tube surfaces. (May 2018) - Haas, C.; Kaiser, F.; Schulenberg, T.; Wetzel, T.
Highlights: Optical observation of critical heat flux (CHF) in vertical annulus for Zircaloy-4 cladding tubes. Fast shutdown avoids damage of the cladding tubes, allowing a statistical observation of the tubes. Different surface structures were applicated on the Zircaloy-4 cladding tubes. The surface structure influence of CHF is pressure and mass flow dependent. A CHF increase of up to 29% was achieved for some surface structures. Abstract: We investigated the influence of surface structure on critical heat flux (CHF) for flow boiling of water. The objectives were to find suitable surface modification processes for Zircaloy-4 tubes and to test their critical heat flux performance in comparison to the smooth surface tube. Surface structures with micro-channels, porous layer, oxidized layer, and elevations in micro- and nanoscale were produced on Zircaloy-4 cladding tube. These modified tubes were tested in an internally heated vertical annulus with a heated length of 326 mm and an inner and outer diameter of 9.5 and 18 mm. The flow boiling experiments with water were performed with mass fluxes of 250 and 400 kg/(m 2  s), outlet pressures between 120 and 300 kPa, and an inlet subcooling temperature of 40 K. Only a small influence of modified surface structures on critical heat flux was observed for the pressure of 120 kPa in the present test section geometry. However, with increased pressure and mass flux, the critical heat flux could be increased up to 29% higher than for the smooth tube using surface structured tubes with micro-channels, porous and oxidized layers. The flow boiling process and the critical heat flux occurrence were visualized by high-speed camera records. Additionally, we characterized the surface wettability behavior of the different tube surfaces using the Wilhelmy method. Concluding from the different characteristics capillary effects and/or increased nucleation site density were assumed to influence the critical heat flux performance.